Practical Applications of Virtual Reality in Continuing Education: a Review of the Case of Secondary Occupational Education - Ghafar, Zanyar Nathir (MultiTech Publisher, 2024)
This paper explores the use of virtual reality in secondary vocational education, highlighting its potential benefits and challenges. Virtual reality provides interactive simulations of real-world work situations, boosting student engagement and knowledge retention. Case studies demonstrate its effectiveness in vocational education and training programs. However, the paper also addresses the financial implications of acquiring software and hardware, as well as the need for specialist technical assistance. The study aims to analyze potential research areas and the future of work, presenting a hopeful and exciting tool for future vocational education. Overall, virtual reality offers promising and exciting solutions for vocational education.